Nothingness, Oneness, and Infinity: Transcendent Experience as a Promising Frontier for Religion and Health Research - Levin, Jeff (Journal of religion and health, 2023)
This paper advocates for a renewed focus into the experiential domain of religious and spiritual expression in research on physical and mental health. Most studies, up to now, have investigated risk or protection associated with behavioral measures of religiousness, whether public behaviors such as religious attendance or private behaviors such as personal prayer. Religious attitudes, beliefs, and identity have been studied, as well, as have religious self-rating scales of various types, but, relatively less emphasized have been subjective experiences, such as feelings of transcendence or unitive connection with the divine. There is good reason to believe that such experiences may impact on well-being, based both on previous studies and on theory and clinical observation. This paper suggests that although researching the domain of such seemingly ineffable experiences may present certain conceptual and methodological challenges, these would be worth facing in order to gain deeper insight into the human spiritual dimension and into connections among body, mind, and spirit.